PENGEMBANGAN BUMDeS SYARIAH DALAM MEMBANGUN EKONOMI BERKEADILAN DI DESA - Venny Syaharany; Putri Rahmaini (Universitas Muhammadiyah Lampung, 2023)
ABSTRACTÂ The village is the smallest unit in a country with the lowest government authority to regulate the interests of the local community. Village Owned Enterprises (BUMDes) are business entities owned by villages to improve community welfare through economic ventures. The development of Sharia-based BUMDes based on sharia principles is one way to achieve this goal. This study used the library research method using library data in the form of books. BUMDes is a business entity whose capital is owned by the village and has developed in many villages in Indonesia, but the majority of BUMDes still use the conventional system and have not implemented a profit-sharing system (sharia). The concept of developing Sharia BUMDes is based on laws and regulations governing the establishment of BUMDes. The development of Sharia BUMDes is expected to increase the religious values of the village community and have a positive impact on their economic life and can provide halal and blessed business results.Â Keyword: BUMDes Sharia, Economic Development, Â